Energy and wood in the French Alps: strategies for an uncertain resource - Hélène Avocat*; Antoine Tabourdeau*; Christophe Chauvin; Marie-Hélène De Sede Marceau (Revue de Géographie Alpine)
During the last decade, fuelwood has developed in the alpine territories under voluntarist policies. Facing a next shortage of sawmill by-products, widely used for paper, chipboards and pellets, forest chips are bound to develop for industrial or local use. This is an opportunity for the alpine forests and territories, of which, nevertheless, vulnerability must be taken in account. Studying policies and instruments shows very contrasted approaches, which could generate tensions on the resource, and behaviors in possible contradiction with de development of a true green energy, such as: increase of transport lengths and then of pollutants emissions, degradation of the environment, and loss of the multifunctionality of the forests.